Experimental Verification of a Leaky-Wave Antenna Based on Bianisotropic Huygens’ Metasurface - Abdo-Sánchez, María Elena; Chen, Michael; Epstein, Ariel; Eleftheriades, George V. (My University, 2019)
Abstract—In this communication, the experimental verification of a leaky-wave antenna that uses a Huygens’ metasurface to have a control on the radiation parameters is addressed. The antenna consists of a parallel-plate waveguide in which the top plate has been replaced by an omega-type bianisotropic Huygens’ metasurface, in order to transform the guided mode into the desired leaky-mode with arbitrary choice of the leakage rates, pointing direction and waveguide height. The physical implementation of the metasurface is explained. Two design examples, radiating at broadside with different leakage factors, are implemented, manufactured and measured. Simulated and experimental results of the achieved directivity, scanning performance and radiation patterns are provided, experimentally corroborating the concept
Keywords: Antenas-Congresos; bianisotropy; Huygens’ metasurface; leaky-wave antenna; measurement; radiation